(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background : Urgent MRI (Magnetic Resonance Imaging) in clinical management is quite often required in the modern hospitals. In many cases, it may be needed for emergency patients and may save a valuable life. A few previous papers show MRI provision needs to be improved and many clinical situations need urgent MRI for management. This project was done with the objective to explore the range of urgent applications of MRI and aim to provide information supporting development of MRI service with the null hypothesis: "there is no need to introduce on call service for urgent MRI”. Materials and methods: This thesis explored the applications of MRI as urgent investigations both retrospectively and prospectively in the busy MRI unit of the John Radcliffe Hospital, Oxford, UK, from 2004 to 2005.To assess the necessity of introducing an on-call service in the unit, a null hypothesis was developed: "There is no need to introduce on call service for urgent MRI”. To test the hypothesis, patients’ records were analysed to observe the effect in clinical management of MRI carried out as an urgent basis. Results: The results explored the demographic trend, common examination areas, types of indications and the nature of MRI reports among the urgent patient referrals. The retrospective and prospective results showed similarity between the two years’ practices. The results of clinical effect of urgent MRI were found to be positive in the majority cases and the null hypothesis was rejected. Conclusion: Overall, the thesis argues that the urgent MRI is not being carried out sufficiently in comparison to routine MRI, although urgent MRI has a good effect on clinical management. The study showed the necessity to develop the on call service in MRI. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 14-18